A practical assessment of wheelchair racing performance kinetics using accelerometers. Issue 8 (17th November 2021) - Lewis, Amy R.; Phillips, Elissa J.; Robertson, William S. P.; Grimshaw, Paul N.; Portus, Marc; Winter, Joseph
ABSTRACT: Due to the detrimental influence of unnecessary mass on performance, racing wheelchair instrumentation used in both competition assessment and research is currently limited. Attaining key kinetic parameters of propulsion can enhance technique and provide athletes with a competitive advantage. This research examined the plausibility of inertial measurement units (IMUs) to estimate propulsion forces, during a simulated wheelchair race start and training. Start propulsion data calculated from an IMU system was compared to reference force plate data; steady state motion data was compared with existing literature. Some agreement in kinetic parameters between IMU data was observed under steady state motion, with data from athletes following a linear force–velocity relationship. In this context, it is important to identify that this cannot be directly compared to the existing literature due to the different methods of force measurement and the lack of data for similar force measurements using IMUs. IMUs were ineffective when used with wheelchairs having spoked wheels. Performance was best for measurements in the direction of motion. Although exact agreement was not observed, the IMU can provide an effective tool in the in-field assessment of propulsion kinetics.